Ethnomedicinal Uses of Plant Resources in Bethanchowk Rural Municipality of Kavrepalanchowk District, Central Nepal - Munankarmi, Nabin Narayan; Chaudhary, Sujan; Neupane, Sanju; Shyaula, Sajan Lal; Zhang, Wei; Gauchan, Dhurva Prasad (Ethnobotany Research and Applications, 2025)
Background: The rural people from different ethnic groups in Nepal possess vast knowledge regarding medicinal plants and their use in the treatment of human ailment. The aim of this study is to record the local’s knowledge about traditional medicine in Bethanchowk Rural Municipality, Central Nepal. Methods: The ethnomedicinal information was collected with the help of door-to-door interviews and focus group discussions using open ended questionnaire with local people and key informants. A linear regression and Spearman correlation were performed to observe the relationship between the age of respondents and the number of plants described by them. The quantitative data were analyzed by informant consensus factor (ICF) and fidelity level (FL). Results: The present study has recorded 227 medicinal plant species under 94 families and 200 genera. The most frequently occurring plants were herbs (n = 103) and leaves (n = 54) as plant parts. There was no significant difference (p = 0.401) in the knowledge of medicinal plants possessed and the number of plants described by the genders. The Spearman correlation (ρ = 0.225) and linear regression justified the weak relationship between the age of the respondents and the number of plants described by them. The ICF value ranged from 0.5 to 0.93, and the highest was observed for gynecological disorder. The FL value ranged from 6.94 to 98.20, with the highest for Ageratina adenophora for bleeding, cuts, and wounds. Conclusion: The traditional medicinal knowledge of local people of Bethanchowk Rural Municipality has been documented in the study. The necessity for such additional documentation and scientific validation of recorded species has been determined by the current investigation. Keywords: Traditional knowledge, ICF, FL, ailments, knowledge transfer